Hypoglycemia in patients with COVID-19: risk factors and prevention of complications - O. A. Halushko; O. V. Protsiuk; O. I. Pohorila (Zaporožskij Medicinskij Žurnal)
The aim of the work is to analyze the available scientific information and generalize the main results of modern research on the causes and risk factors of hypoglycemia in patients with COVID-19.